Nano calcite (CaCO3) production in semi-batch bubble reactor - Ülkeryıldız, Eda; Özdemir, Ekrem (Izmir Institute of Technology, 2013)
Calcium carbonate (CaCO3) has been widely used as filling material in many industries due to its low cost and enhancement in some of the physical properties of the composite materials. The main purpose of this study was to produce CaCO3 particles by carbonation method in nano size, homogeneous size distribution and different morphologies. A semi-batch bubble reactor was designed in order to introduce carbon dioxide (CO2) into the Ca(OH)2 solution or its slurry with a controlled fashion. Different parameters such as stirring rate, Ca(OH)2 concentration, CO2 flow rate, and pulse CO2 injection were examined. Also, jet flow was applied in the stirred tank reactor to prevent particles from aggregation. Conductivity and pH values of solutions were monitored during crystallization. Zeta potential values and average particle size were measured instantly by dynamic light scattering (DLS). Particles produced were separated by centrifugation, dried at 105 oC in an oven for 1 day, and characterized by the Scanning Electron Microscopy (SEM) for their morphology, and X-Ray diffraction (XRD) for their crystal structures. On the basis of XRD analysis, the main crystal form of precipitated particles was calcite. According to SEM images, elongated chain-like, cubical, and rectangular particles were achieved to be produced with particle size of about 200 nm to 400 nm.
Thesis (Master)--Izmir Institute Of Technology, Chemical Engineering, Izmir, 2013
Includes bibliographical references (leaves: 119-125)
Text in English; Abstract: Turkish and English
xv, 125 leaves
Keywords: Calcite; Calcium carbonate; Crystallization